Influence of side-chain interactions on the self-assembly of discotic tricarboxyamides: a crystallographic insight1. Issue 40 (7th May 2015) - Paikar, Arpita; Pramanik, Apurba; Haldar, Debasish
<x xml:space="preserve">Abstract</x> Side chains interactions promote the self-assembly of discotic tricarboxyamides to form an entangled fiber network and thermo responsive gel.